The role of natural scientists in navigating the social implications of cellular agriculture: insights from an interdisciplinary workshop - Rao, Varsha V.; Datta, Bianca; Steinmetz, Kai (Frontiers in Sustainable Food Systems, 2023)
The emerging field of cellular agriculture uses cell culture to create animal products, potentially mitigating climate and health risks associated with conventional animal agriculture. However, cellular agriculture products are poised to enter the food system without an understanding of the long-term consequences and social implications. While these discussions have begun among social scientists, dialogues are lacking among natural scientists, perpetuating a disconnect between those progressing new technology and those directly impacted by it. To begin to bridge this gap, an interdisciplinary workshop was organized by the Food and Agriculture Institute at the University of the Fraser Valley in collaboration with the Arrell Food Institute, New Harvest, and Cellular Agriculture Canada, to convene representatives from cellular agriculture companies, STEM research labs, dairy farms, animal rights organizations, and Indigenous communities to discuss the social implications of cellular agriculture. In this commentary, the authors highlight critical learnings for natural scientists, namely the relationship between food and identity, human-animal relationships, implications for nutrition and health, and cost and accessibility. Based on these concerns, we highlight specific areas of research that technical scientists should explore and provide examples of guidelines, such as responsible research and innovation frameworks, to help natural scientists and engineers better engage with the social implications of their research. As we rapidly approach a food system that includes cellular agriculture products, we encourage readers to involve broader populations in this growth and to create pathways that ensure socially responsible development of the field.